Minangkabau Community in the Collection of Kaki Yang Terhormat Short Story by Gus Tf Sakai - Habibullah Karami; Aruna Laila; Wahyudi Rahmat (Bahasa: Jurnal Keilmuan Pendidikan Bahasa dan Sastra Indonesia, 2019)
The problem in this study is the many forms of social reality of the Minangkabau people in Collection of Kaki Yang Terhormat Short Story by Gus Tf Sakai. This problem is the main reference to find out what the social reality of the Minangkabau community is in the Collection of Kaki Yang Terhormat Short Story by Gus Tf Sakai from the perspective of the author. This type of research is qualitative research. The method used in this research is descriptive method. The data in this study are in the form of words, sentences and dialogues related to Minangkabau social reality. The data source in this study is a Collection of Kaki Yang Terhormat Short Story by Gus Tf Sakai. The results of this studyillustrate the social reality of the Minangkabau people that occur from cultures or  traditions that have been born from their ancestors, which are customs or that have become identities for the people in Minangkabau or from habits that occur repeatedly and are designated as traditions for the Minangkabau people. Based on this, social reality of the Minangkabau people in Collection of Kaki Yang Terhormat Short Story by Gus Tf Sakai in terms of (1) language, there are Minang languages and Indonesian languages; (2) the science system, regarding takambang nature to become a teacher; (3) social systems / social systems, in the form of traditions that become the identity of the Minangkabaucommunity; (4) equipment / equipment, regarding equipment / characteristics for the Minangkabau community which is a necessity for life and culture of the Minangkabau community; (5) livelihood system, regarding work for the Minangkabau people (6) arts, concerning the motion art possessed by the Minangkabau people namely silek, and (7) religious systems, regarding culture to surau for adolescents in Minangkabau.